Analisis Kepuasan Konsumen Terhadap E- Service Quality Gofood di Kota Mataram - Rusminah Rusminah; Hilmiati Hilmiati; H.M. Ilhamudin (Universitas Mataram, 2022)
The Research is conducted to satisfation for E-quality to use toward the using of GoFood application at consumers' in Mataram city. This type of research is an associate study. The population in this research is Mataram city comminity that uses GoFood application, with a sample of 100 responden. Sample technique use Non probability samplig with Purposive sampling method. The data-collection techniques used, angket and documentation. The analysis technique which is applied to examine is Consumer Satisfaction Index Analysis and Cartesian Diagram Analysis. The research result shows that there is a positive influence and significant of perceived usefulness and petceived ease of use toward the using of GoFood application at consumers’ in Mataram city, hence it is recommended to Gojek workers to make more impact on services and security and to continue recovery by promoting technological ease, enabling consumers to interact more easily, conveniently and safely